Potassium jarosite electrode material and preparation method and application thereof

By using hydrothermal reaction and alcohol solution reaction methods in the preparation of yellow potassium iron alum electrode material, the problem of using strong acid solutions in the prior art is solved, and the preparation of green and environmentally friendly and simple processes is realized, and the positive electrode material of sodium ion battery is carried out. Excellent electrochemical properties are shown.

CN119490231AActive Publication Date: 2025-02-21WUHAN UNIV OF TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411669729.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-21
Estimated Expiration
2044-11-21

Smart Images

  • Figure CN119490231A_ABST
    Figure CN119490231A_ABST
Patent Text Reader

Abstract

The invention provides a jarosite electrode material as well as a preparation method and application thereof, and relates to the field of sodium ion battery positive electrode materials. The preparation method of the jarosite electrode material comprises the following steps: mixing potassium permanganate, a high-molecular polymer and water for hydrothermal reaction to obtain hydroxyl manganese oxide; manganese oxyhydroxide and absolute ethyl alcohol are mixed to prepare an alcoholic solution of manganese oxyhydroxide, and the alcoholic solution reacts with a mixed solution containing ferrous sulfate salt and sylvite to obtain jarosite. The preparation method of the jarosite electrode material disclosed by the invention does not need to use a strong acid solution, is mild in reaction condition, simple in process and simple and convenient to operate and has a good industrial application prospect, and the jarosite electrode material shows good electrochemical performance, good long-term cycle stability and high rate capability when being used as a sodium-ion battery positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion battery positive electrode materials, and in particular to a jarosite electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, the shortage and uneven distribution of lithium resources have become increasingly prominent. In contrast, sodium-ion batteries have continued to attract more and more research due to their rich raw material sources and low costs. In sodium-ion battery systems, the performance of cathode materials directly affects the energy density and production cost of the battery. Therefore, it is particularly important to develop cathode materials with high energy density, high safety and low cost. Iron-based sulfate (such as yellow potassium ferrosite) cathodes have attracted much attention due to their rich raw material sources, low cost and high operating voltage. In addition, the crystal structure of yellow potassium ferrosite is arranged in layers, providing a fast ion diffusion channel. In recent years, literature on the preparation of yellow potassium ferrosite has been reported, but most of them use hydrothermal or solvothermal methods, and strong acid solutions are used in the synthesis process. These methods are complex, time-consuming and have certain risks. Therefore, it is urgent to develop a green and environmentally friendly method for preparing yellow potassium ferrosite with mild reaction conditions. Summary of the invention

[0003] The purpose of the present invention is to provide a jarosite electrode material and a preparation method and application thereof, so as to solve the problems that the existing jarosite electrode material needs to use a strong acid solution during the preparation process and the method is complicated and time-consuming.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a jarosite electrode material, comprising the following steps:

[0006] 1) mixing potassium permanganate, a high molecular polymer and water to perform a hydrothermal reaction to obtain manganese oxyhydroxide;

[0007] 2) Mixing manganese oxyhydroxide with anhydrous ethanol to prepare an alcohol solution of manganese oxyhydroxide, and reacting the solution with a mixed solution containing ferrous sulfate and potassium salt to obtain jarosite electrode material.

[0008] Preferably, the mass ratio of potassium permanganate, high molecular polymer and water in step 1) is 0.15-0.3 g: 0.05-0.1 g: 150-170 mL;

[0009] The high molecular polymer includes one or more of polyvinyl pyrrolidone, polyvinyl alcohol and polyacrylic acid.

[0010] Preferably, the temperature of the hydrothermal reaction in step 1) is 120-160° C. and the time is 25-30 hours.

[0011] Preferably, the molar ratio of manganese oxyhydroxide, ferrous sulfate and potassium salt in step 2) is 3:2 to 3:1;

[0012] The addition ratio of manganese oxyhydroxide to anhydrous ethanol is 0.0045 mol: 40-60 mL;

[0013] The addition ratio of the ferrous sulfate salt, potassium salt and water is 0.003-0.0045 mol: 0.0015 mol: 15-40 mL.

[0014] Preferably, the reaction temperature in step 2) is 60-90° C., and the reaction time is 3-12 h.

[0015] Preferably, the potassium salt in step 2) includes one or more of potassium nitrate, potassium chloride and potassium sulfate;

[0016] The ferrous sulfate salt includes one or more of ferrous sulfate, ferrous sulfate pentahydrate, ammonium ferrous sulfate hexahydrate, and ferrous sulfate heptahydrate.

[0017] The present invention also provides a jarosite electrode material prepared by the above preparation method.

[0018] The present invention also provides an application of the above-mentioned jarosite electrode material in a positive electrode material for a sodium ion battery. The preparation method of the positive electrode material for a sodium ion battery is as follows:

[0019] The jarosite electrode material, water and carbon nanotubes are mixed to obtain a suspension, and the suspension is filtered to obtain a jarosite self-supporting electrode.

[0020] Preferably, the mass ratio of the jarosite electrode material to the carbon nanotubes is 1:31.25-125.

[0021] The present invention has at least the following beneficial effects:

[0022] 1. The method for preparing the jarosite electrode material disclosed in the present invention does not require the use of a strong acid solution, has mild reaction conditions, a simple process, and is easy to operate, and has good prospects for industrial application.

[0023] 2. The jarosite prepared by the present invention exhibits good electrochemical properties when used as a positive electrode material for sodium ion batteries, good long-term cycle stability, and high rate performance. It is an ideal positive electrode material for sodium ion batteries with broad commercial application prospects.

[0024] 3. The substrate-free self-supporting jarosite electrode does not contain inert binder particles, has a continuous electronic conductive path, and the active material is tightly wrapped in a three-dimensional conductive network, which improves the electronic conductivity of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The X-ray diffraction pattern of the manganese oxyhydroxide prepared in Example 1;

[0026] Figure 2 is a scanning electron microscope image of the manganese oxyhydroxide prepared in Example 1;

[0027] Figure 3 The X-ray diffraction pattern of the jarosite prepared in Example 1;

[0028] Figure 4 This is a scanning electron microscope image of the jarosite prepared in Example 1;

[0029] Figure 5 is the X-ray photoelectron spectrum of the jarosite prepared in Example 1;

[0030] Figure 6 This is the infrared spectrum of the jarosite prepared in Example 1;

[0031] Figure 7 The cyclic voltammetry curve of the jarosite self-supporting electrode prepared in Example 1 in an organic sodium ion battery;

[0032] Figure 8 The charge and discharge curve of the jarosite self-supporting electrode prepared in Example 1 in an organic sodium ion battery;

[0033] Fig. 9 This is a rate performance diagram of the jarosite self-supporting electrode prepared in Example 1 in an organic sodium ion battery;

[0034] Fig.10 This is the cycle curve of the jarosite self-supporting electrode prepared in Example 1 in an organic sodium ion battery. DETAILED DESCRIPTION

[0035] The present invention provides a method for preparing a jarosite electrode material, comprising the following steps:

[0036] 1) mixing potassium permanganate, a high molecular polymer and water to perform a hydrothermal reaction to obtain manganese oxyhydroxide;

[0037] 2) Mixing manganese oxyhydroxide with anhydrous ethanol to prepare an alcohol solution of manganese oxyhydroxide, and reacting the solution with a mixed solution containing ferrous sulfate and potassium salt to obtain jarosite electrode material.

[0038] In the present invention, the mass ratio of potassium permanganate, high molecular polymer and water in step 1) is 0.15-0.3g:0.05-0.1g:150-170mL, preferably 0.17-0.28g:0.06-0.09g:155-165mL, further preferably 0.2-0.25g:0.07-0.08g:158-163mL, more preferably 0.22-0.24g:0.07-0.08g:160mL.

[0039] In the present invention, the temperature of the hydrothermal reaction in step 1) is 120-160°C, preferably 125-155°C, more preferably 130-150°C, and more preferably 135-140°C; the time is 25-30h, preferably 26-29h, and more preferably 27-28h.

[0040] In the present invention, the molar ratio of manganese oxyhydroxide, ferrous sulfate and potassium salt in step 2) is 3:2-3:1, preferably 3:2.2-2.8:1, more preferably 3:2.4-2.6:1, and more preferably 3:2.5:1.

[0041] In the present invention, the addition ratio of manganese oxyhydroxide to anhydrous ethanol is 0.0045 mol: 40-60 mL, preferably 0.0045 mol: 45-55 mL, and more preferably 0.0045 mol: 50 mL.

[0042] In the present invention, the addition ratio of the ferrous sulfate salt, potassium salt and water is 0.003-0.0045 mol: 0.0015 mol: 15-40 mL, preferably 0.0032-0.0042 mol: 0.0015 mol: 20-35 mL, and more preferably 0.0035-0.004 mol: 0.0015 mol: 25-30 mL.

[0043] In the present invention, the reaction temperature in step 2) is 60-90°C, preferably 65-85°C, more preferably 70-80°C, and more preferably 75°C; the reaction time is 3-12h, preferably 5-10h, more preferably 6-9h, and more preferably 7-8h.

[0044] In the present invention, the potassium salt in step 2) includes one or more of potassium nitrate, potassium chloride and potassium sulfate;

[0045] In the present invention, the ferrous sulfate salt includes one or more of ferrous sulfate, ferrous sulfate pentahydrate, ammonium ferrous sulfate hexahydrate, and ferrous sulfate heptahydrate.

[0046] The present invention also provides a jarosite electrode material prepared by the above preparation method.

[0047] The present invention also provides an application of the above-mentioned jarosite electrode material in a positive electrode material for a sodium ion battery. The preparation method of the positive electrode material for a sodium ion battery is as follows:

[0048] The jarosite electrode material, water and carbon nanotubes are mixed to obtain a suspension, and the suspension is filtered to obtain a jarosite self-supporting electrode.

[0049] In the present invention, the mass ratio of the jarosite electrode material to the carbon nanotubes is 1:31.25-125, preferably 1:40-110, more preferably 1:50-100, and even more preferably 1:60-90.

[0050] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0051] Example 1

[0052] 1) Dissolve 0.084g polyvinyl pyrrolidone and 0.168g potassium permanganate in 160mL deionized water, stir for 50min, transfer to a 200mL reactor, and then heat at 140°C for 25h in an electric blast drying oven for hydrothermal reaction. After the reaction, separate the solvent and dry to obtain hydroxyl manganese oxide nanowires. The X-ray diffraction spectrum of hydroxyl manganese oxide nanowires is as follows: Figure 1 As shown, from Figure 1 It can be seen that the diffraction peaks are sharp and strong, and all the diffraction peaks of the product are consistent with the standard diffraction peaks of manganese oxyhydroxide (JCPDS Card No. 41-1379), and no impurity absorption peaks are observed, indicating that the product is of high purity; the scanning electron microscope image of manganese oxyhydroxide nanowires is shown in Figure 2 As shown, from Figure 2 It can be seen that the manganese oxyhydroxide nanowires grow very neatly and smoothly, and are large in scale. The length of the manganese oxyhydroxide nanowires is about 5 to 10 μm, and the diameter is about 70 to 100 nm.

[0053] 2) 0.393 g (0.0045 mol) of manganese oxyhydroxide was ultrasonically dispersed in 50 mL of anhydrous ethanol to obtain a uniform dispersion. 1.2552 g (0.0045 mol) of ferrous sulfate heptahydrate and 0.1526 g (0.0015 mol) of potassium nitrate were dissolved in 30 mL of deionized water to obtain a mixed solution of iron ions and potassium ions, which was added dropwise to the ethanol dispersion, and then stirred evenly at room temperature to obtain a reaction precursor solution.

[0054] 3) The obtained reaction precursor solution was transferred to a sealed glass bottle container and placed in a 90°C water bath. After heating and stirring for 3 hours, the reaction solution was naturally cooled. The reaction solution was filtered using a suction filtration device, and then washed with deionized water and anhydrous ethanol to obtain a yellow powder. Finally, the yellow powder was placed in an 80°C air drying oven and dried for 24 hours to obtain a yellow jarosite electrode material. The X-ray diffraction pattern of the yellow jarosite electrode material is shown in FIG. Figure 3 As shown, from Figure 3 It can be seen that the obtained product is completely consistent with the standard card (JCPDS Card No. 22-0827), with no impurity peaks, indicating that the synthesized substance is jarosite, and the diffraction peak is sharp, indicating that the product has good crystallinity; the scanning electron microscope image of the jarosite electrode material is as follows Figure 4 As shown, from Figure 4 It can be seen that more polyhedral structure products are formed, and the crystal structure is good; the X-ray photoelectron spectrum of the jarosite electrode material is as follows Figure 5 As shown, from Figure 5 The relevant characteristic peaks of K, Fe, S, and O can be observed, and there are no other impurity peaks, which proves that the purity of the synthesized sample is very high; the infrared spectrum of the jarosite electrode material is shown in Figure 6 As shown, from Figure 6 It can be seen that 500~1400cm -1 The range is SO4 2- Overlapping vibration modes, 1100cm -1 The bands near are attributed to tetrahedral SO4 2- Asymmetric stretching, and located at 1010cm -1 The peak reflects the SO4 2- Tensile vibration, about 3450cm -1 The peak at corresponds to OH — vibration.

[0055] Preparation and performance test of self-supporting jarosite cathode:

[0056] Weigh 10 mg of the yellow jarosite electrode material prepared in this embodiment and put it into a glass bottle, add 15 mL of deionized water, use an ultrasonic cell crusher to ultrasonically disperse for 10 minutes, and obtain a uniform yellow suspension; add 0.625 g of carbon nanotube slurry (the content of carbon nanotubes is 0.4wt%, and the dispersant is water) to the suspension, and then use an ultrasonic cell crusher to ultrasonically disperse for 40 minutes to obtain a black suspension containing yellow jarosite and carbon nanotubes. The black suspension is quickly filtered using a sand core funnel, and a black film is obtained on the filter membrane after the filtration is completed. The film is placed in a cool place indoors to dry, and the black film falls off the filter membrane after drying, and the yellow jarosite sodium ion battery positive electrode material is obtained.

[0057] The above-mentioned jarosite sodium ion battery positive electrode material was pressed into a 12 mm electrode sheet using a tablet press, and a 1 mol / L electrolyte was prepared using glass fiber as a separator, diethylene glycol dimethyl ether as a solvent, and sodium hexafluorophosphate as an electrolyte. A pure sodium sheet was used as a counter electrode and assembled into a button cell for electrochemical performance testing.

[0058] Figure 7 The cyclic voltammetry curves of the button cell prepared in this example at different scan rates show that the cyclic voltammetry curve has a broad and inconspicuous redox peak, which is an obvious pseudocapacitive behavior. And as the scan rate increases, the peak point shifts slightly.

[0059] Figure 8 The charge and discharge curves of the button battery prepared in this example at different rates do not have a platform at a relatively small (0.1C) or large (30C) rate, which is consistent with Figure 7 This corresponds to the broad and inconspicuous redox peak in the cyclic voltammetry curve in , proving that the prepared jarosite is a pseudocapacitive electrode material.

[0060] Fig. 9 The rate performance diagram of the button cell prepared in this embodiment shows that as the rate increases from 0.2C to 0.5C, 1C, 2C, 5C, 10C, 20C, and 30C (1C = 160.5 mAg -1 ), and the reversible capacities are 120.5, 118.0, 109.8, 106.9, 95.9, 88.4, 78.9, and 72.2 (all in mAh g -1 ), when the current density returned to 0.2C, the reversible capacity increased to 119.2 mAh g -1 Even at a rate of 30C, it still has 72.2mAh g -1 The specific capacity of 2.547 W / m2 (about 61.18% at 0.5 C) indicates that the prepared jarosite cathode exhibits excellent rate performance.

[0061] Fig.10 mA g -1 The cycling performance diagram shows that the capacity is 58.87 mAh g after 1000 cycles at 2C and 5C rates, respectively. -1 and 52.0mAh g -1 The specific capacity of the prepared jarosite cathode exhibits good cycle stability.

[0062] Example 2

[0063] 1) 0.090 g of polyvinyl pyrrolidone and 0.18 g of potassium permanganate were dissolved in 160 mL of deionized water, stirred for 50 min, transferred to a 200 mL reactor, and then heated in an electric blast drying oven at 140 ° C for 28 h for hydrothermal reaction. After the reaction, the solvent was separated and dried to obtain hydroxyl manganese oxide nanowires.

[0064] 2) 0.393 g (0.0045 mol) of manganese oxyhydroxide was ultrasonically dispersed in 40 mL of anhydrous ethanol to obtain a uniform dispersion. 0.8368 g (0.003 mol) of ferrous sulfate heptahydrate and 0.1526 g (0.0015 mol) of potassium nitrate were dissolved in 35 mL of deionized water to obtain a mixed solution of iron ions and potassium ions, which was added dropwise to the ethanol dispersion, and then stirred evenly at room temperature to obtain a reaction precursor solution.

[0065] 3) The obtained reaction precursor solution was transferred to a sealed glass bottle container and placed in an 80°C water bath. After heating and stirring for 5 hours, it was naturally cooled. The reaction solution was filtered using a suction filtration device, and then washed with deionized water and anhydrous ethanol respectively to obtain a yellow powder. Finally, it was placed in an 80°C forced air drying oven and dried for 24 hours to obtain the yellow potassium ferroaluminate electrode material.

[0066] Preparation and performance test of self-supporting jarosite cathode:

[0067] Weigh 10 mg of the yellow jarosite electrode material prepared in this embodiment and put it into a glass bottle, add 15 mL of deionized water, use an ultrasonic cell crusher to ultrasonically disperse for 10 minutes, and obtain a uniform yellow suspension; add 0.625 g of carbon nanotube slurry (the content of carbon nanotubes is 0.4wt%, and the dispersant is water) to the suspension, and then use an ultrasonic cell crusher to ultrasonically disperse for 40 minutes to obtain a black suspension containing yellow jarosite and carbon nanotubes. The black suspension is quickly filtered using a sand core funnel, and a black film is obtained on the filter membrane after the filtration is completed. The film is placed in a cool place indoors to dry, and the black film falls off the filter membrane after drying, and the yellow jarosite sodium ion battery positive electrode material is obtained.

[0068] The above-mentioned jarosite sodium ion battery positive electrode material was pressed into a 12 mm electrode sheet using a tablet press, and a glass fiber was used as a separator, diethylene glycol dimethyl ether was used as a solvent, and sodium hexafluorophosphate was used as an electrolyte to prepare an electrolyte with a concentration of 1 mol / L. Pure sodium sheet was used as a counter electrode to assemble into a button cell for electrochemical performance testing. When the current density was 0.5C, its reversible capacity was 113.8 mAh g -1 ; After 1000 cycles at 2C and 5C rates, the capacity is 58.42 mAh g -1 and 54.06mAh g -1 .

[0069] Example 3

[0070] 1) 0.1 g of polyvinyl alcohol and 0.3 g of potassium permanganate were dissolved in 170 mL of deionized water, stirred for 50 min, and then transferred to a 200 mL reactor, and then heated in an electric blast drying oven at 140° C. for 25 h for hydrothermal reaction. After the reaction was completed, the solvent was separated and dried to obtain manganese oxide hydroxide nanowires.

[0071] 2) 0.393 g (0.0045 mol) of manganese oxyhydroxide was ultrasonically dispersed in 50 mL of anhydrous ethanol to obtain a uniform dispersion. Then 1.2552 g (0.0045 mol) of ferrous sulfate heptahydrate and 0.1526 g (0.0015 mol) of potassium nitrate were dissolved in 40 mL of deionized water to obtain a mixed solution of iron ions and potassium ions, which was added dropwise to the ethanol dispersion, and then stirred evenly at room temperature to obtain a reaction precursor solution.

[0072] 3) The obtained reaction precursor solution was transferred to a sealed glass bottle container and placed in a 60°C water bath. After heating and stirring for 10 hours, it was naturally cooled. The reaction solution was filtered using a suction filtration device, and then washed with deionized water and anhydrous ethanol to obtain a yellow powder. Finally, it was placed in an 80°C forced air drying oven and dried for 24 hours to obtain the yellow potassium ferroaluminate electrode material.

[0073] Preparation and performance test of self-supporting jarosite cathode:

[0074] Weigh 10 mg of the yellow jarosite electrode material prepared in this embodiment and put it into a glass bottle, add 15 mL of deionized water, use an ultrasonic cell crusher to ultrasonically disperse for 10 minutes, and obtain a uniform yellow suspension; add 0.625 g of carbon nanotube slurry (the content of carbon nanotubes is 0.4wt%, and the dispersant is water) to the suspension, and then use an ultrasonic cell crusher to ultrasonically disperse for 40 minutes to obtain a black suspension containing yellow jarosite and carbon nanotubes. The black suspension is quickly filtered using a sand core funnel, and a black film is obtained on the filter membrane after the filtration is completed. The film is placed in a cool place indoors to dry, and the black film falls off the filter membrane after drying, and the yellow jarosite sodium ion battery positive electrode material is obtained.

[0075] The above-mentioned jarosite sodium ion battery positive electrode material was pressed into a 12 mm electrode sheet using a tablet press, and a glass fiber was used as a separator, diethylene glycol dimethyl ether was used as a solvent, and sodium hexafluorophosphate was used as an electrolyte to prepare an electrolyte with a concentration of 1 mol / L. Pure sodium sheet was used as a counter electrode to assemble into a button cell for electrochemical performance testing. When the current density was 0.5C, its reversible capacity was 123.1 mAh g -1 ; After 1000 cycles at 2C and 5C rates, the capacity is 57.33 mAh g -1and 52.74mAh g -1 .

[0076] Example 4

[0077] 1) 0.065 g of polyvinyl pyrrolidone and 0.25 g of potassium permanganate were dissolved in 150 mL of deionized water, stirred for 50 min, transferred to a 200 mL reactor, and then heated in an electric blast drying oven at 140 ° C for 25 h for hydrothermal reaction. After the reaction, the solvent was separated and dried to obtain hydroxyl manganese oxide nanowires.

[0078] 2) 0.393 g (0.0045 mol) of manganese oxyhydroxide was ultrasonically dispersed in 50 mL of anhydrous ethanol to obtain a uniform dispersion. 1.2552 g (0.0045 mol) of ferrous sulfate heptahydrate and 0.1526 g (0.0015 mol) of potassium nitrate were dissolved in 30 mL of deionized water to obtain a mixed solution of iron ions and potassium ions, which was added dropwise to the ethanol dispersion, and then stirred evenly at room temperature to obtain a reaction precursor solution.

[0079] 3) The obtained reaction precursor solution was transferred to a sealed glass bottle container and placed in a 70°C water bath. After heating and stirring for 12 hours, it was naturally cooled. The reaction solution was filtered using a suction filtration device, and then washed with deionized water and anhydrous ethanol respectively to obtain a yellow powder. Finally, it was placed in an 80°C forced air drying oven and dried for 24 hours to obtain the yellow potassium ferroaluminate electrode material.

[0080] Preparation and performance test of self-supporting jarosite cathode:

[0081] Weigh 10 mg of the yellow jarosite electrode material prepared in this embodiment and put it into a glass bottle, add 15 mL of deionized water, use an ultrasonic cell crusher to ultrasonically disperse for 10 minutes, and obtain a uniform yellow suspension; add 0.625 g of carbon nanotube slurry (the content of carbon nanotubes is 0.4wt%, and the dispersant is water) to the suspension, and then use an ultrasonic cell crusher to ultrasonically disperse for 40 minutes to obtain a black suspension containing yellow jarosite and carbon nanotubes. The black suspension is quickly filtered using a sand core funnel, and a black film is obtained on the filter membrane after the filtration is completed. The film is placed in a cool place indoors to dry, and the black film falls off the filter membrane after drying, and the yellow jarosite sodium ion battery positive electrode material is obtained.

[0082] The above-mentioned jarosite sodium ion battery positive electrode material was pressed into a 12 mm electrode sheet using a tablet press, and a glass fiber was used as a separator, diethylene glycol dimethyl ether was used as a solvent, and sodium hexafluorophosphate was used as an electrolyte to prepare an electrolyte with a concentration of 1 mol / L. Pure sodium sheet was used as a counter electrode to assemble into a button cell for electrochemical performance testing. When the current density was 0.5C, its reversible capacity was 124.8 mAh g -1; After 1000 cycles at 2C and 5C rates, the capacity is 56.92 mAh g -1 and 51.55mAh g -1 .

[0083] Comparative Example 1

[0084] Weigh 2.5104 g of ferrous sulfate heptahydrate and 0.3052 g of potassium nitrate and dissolve them in 200 mL of 0.01 mol / L dilute sulfuric acid aqueous solution, and mix them evenly by ultrasonic dispersion to obtain a reaction precursor solution; place the beaker in a 90°C water bath, heat and stir to react for 3 hours; after natural cooling, use a suction filtration device to filter the reaction solution, and then use deionized water and ethanol to wash and filter 3 times to obtain a yellow powder, and finally place it in an 80°C forced air drying oven to dry for 24 hours to obtain a yellow potassium ferroaluminate electrode material.

[0085] Weigh 10 mg of the yellow jarosite electrode material prepared in this comparative example and put it into a glass bottle, add 15 mL of deionized water, and use an ultrasonic cell crusher to ultrasonically disperse for 10 minutes to obtain a uniform yellow suspension; add 0.625 g of carbon nanotube slurry (the content of carbon nanotubes is 0.4 wt%, and the dispersant is water) to the suspension, and then use an ultrasonic cell crusher to ultrasonically disperse for 40 minutes to obtain a black suspension containing yellow jarosite and carbon nanotubes. The black suspension is quickly filtered using a sand core funnel, and a black film is obtained on the filter membrane after the filtration is completed. The film is placed in a cool place indoors to dry, and the black film falls off the filter membrane after drying, and the yellow jarosite sodium ion battery positive electrode material is obtained.

[0086] The above-mentioned jarosite sodium ion battery positive electrode material was pressed into a 12 mm electrode sheet using a tablet press, and a glass fiber was used as a separator, diethylene glycol dimethyl ether was used as a solvent, and sodium hexafluorophosphate was used as an electrolyte to prepare an electrolyte with a concentration of 1 mol / L. Pure sodium sheet was used as a counter electrode to assemble into a button cell for electrochemical performance testing. When the current density was 0.5C, its reversible capacity was 118.16 mAh g -1 ; After 1000 cycles at 2C and 5C rates, the capacity is 52.095 mAh g -1 and 50.1925mAh g -1 .

[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a jarosite electrode material, characterized in that: The following steps are involved: 1) mixing potassium permanganate, a high molecular polymer and water to perform a hydrothermal reaction to obtain manganese oxyhydroxide; 2) Mixing manganese oxyhydroxide with anhydrous ethanol to prepare an alcohol solution of manganese oxyhydroxide, and reacting the solution with a mixed solution containing ferrous sulfate and potassium salt to obtain jarosite electrode material.

2. The method for preparing a jarosite electrode material according to claim 1, characterized in that: The mass ratio of potassium permanganate, high molecular polymer and water in step 1) is 0.15-0.3 g: 0.05-0.1 g: 150-170 mL; The high molecular polymer includes one or more of polyvinyl pyrrolidone, polyvinyl alcohol and polyacrylic acid.

3. The method for preparing a jarosite electrode material according to claim 2, characterized in that: The temperature of the hydrothermal reaction in step 1) is 120-160° C. and the time is 25-30 hours.

4. The method for preparing a jarosite electrode material according to any one of claims 1 to 3, characterized in that: The molar ratio of manganese oxyhydroxide, ferrous sulfate and potassium salt in step 2) is 3:2 to 3:1; The addition ratio of manganese oxyhydroxide to anhydrous ethanol is 0.0045 mol: 40-60 mL; The addition ratio of the ferrous sulfate salt, potassium salt and water is 0.003-0.0045 mol: 0.0015 mol: 15-40 mL.

5. The method for preparing a jarosite electrode material according to claim 4, characterized in that: The reaction temperature in step 2) is 60-90° C., and the reaction time is 3-12 hours.

6. The method for preparing a jarosite electrode material according to claim 5, characterized in that: The potassium salt in step 2) includes one or more of potassium nitrate, potassium chloride and potassium sulfate; The ferrous sulfate salt includes one or more of ferrous sulfate, ferrous sulfate pentahydrate, ammonium ferrous sulfate hexahydrate, and ferrous sulfate heptahydrate.

7. The jarosite electrode material prepared by the method for preparing a jarosite electrode material according to any one of claims 1 to 6.

8. The use of the jarosite electrode material according to claim 7 in a positive electrode material for a sodium ion battery, characterized in that: The preparation method of the positive electrode material of the sodium ion battery is as follows: The jarosite electrode material, water and carbon nanotubes are mixed to obtain a suspension, and the suspension is filtered to obtain a jarosite self-supporting electrode.

9. The use of the jarosite electrode material according to claim 8 in a positive electrode material for a sodium ion battery, characterized in that: The mass ratio of the jarosite electrode material to the carbon nanotubes is 1:31.25-125.

Citation Information

Patent Citations

  • Method used for preparing hydroxy manganese oxide superfine single crystal nanometer line

    CN102531064A

  • Preparation method of jarosite and CNTs modified compound thereof and application of jarosite and CNTs modified compound thereof in lithium battery electrode material

    CN112310350A

  • Jarosite electrode material and preparation method thereof, and self-supporting electrode and preparation method and application thereof

    CN115377342A

  • Fast-charging organic sodium-ion battery with high specific energy

    CN117766859A

  • Novel fluoro material which may be used as an electrode active material

    US20140306149A1